2022
DOI: 10.1029/2022ja030889
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the ΣO/N2 Depletion With Latitudinally Tilted Equatorward Boundary Observed by GOLD During the Geomagnetic Storm on April 20, 2020

Abstract: A long‐lived (>10 hr) O/N2 column density ratio (∑O/N2) depletion at middle latitudes was observed by the Global‐scale Observations of the Limb and Disk (GOLD) during the 20 April 2020 geomagnetic storm. The observed ∑O/N2 depletion tilts latitudinally at equatorward boundary with the lowest latitude of ∼20°N at ∼75°W, and changes orientation near 75°W, with a north‐westward tilt to the west of ∼75° ${}^{\circ}$W and a north‐eastward tilt to the east of ∼75° ${}^{\circ}$W. The National Center for Atmospheric R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
(92 reference statements)
4
10
0
Order By: Relevance
“…The PC1's structure in the regions between −60 and −90 longitudes and 20°N–60°N latitudes strongly aligns with the ΣO/N 2 depletion structure of the April 2020 geomagnetic storm as reported by Yu et al. (2022). This further suggests a strong influence of the geomagnetic storm on the variations in PC1.…”
Section: Resultssupporting
confidence: 85%
“…The PC1's structure in the regions between −60 and −90 longitudes and 20°N–60°N latitudes strongly aligns with the ΣO/N 2 depletion structure of the April 2020 geomagnetic storm as reported by Yu et al. (2022). This further suggests a strong influence of the geomagnetic storm on the variations in PC1.…”
Section: Resultssupporting
confidence: 85%
“…The ratios of height‐integrated number density of atomic oxygen (O) to that of molecular nitrogen (N 2 ), namely column O/column N 2 density ratio (∑O/N 2 ), which can be deduced by disk‐viewing optical observations of OI 135.6 nm and Lyman‐Birge‐Hopfield radiances (Meier, 2021; Strickland et al., 1995), has been widely utilized to describe thermospheric neutral composition responses to geomagnetic storms and the storm effects on ionospheric plasma density (e.g., Cai et al., 2020, 2021a, 2021b, 2023; Crowley et al., 2006; Eastes et al., 2020; Lee et al., 2013; Liou et al., 2005; Strickland et al., 1999, 2001; Wang et al., 2021; Yu et al., 2022a, 2022b; Zhai et al., 2023; Zhang et al., 2004). Previous studies demonstrated the evolution and physical processes of ∑O/N 2 during geomagnetic storms, which is briefly summarized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Resultingly, enlarged neutral temperatures and vertical winds generate the thermospheric composition disturbance: larger increases of the molecular species relative to the atomic ones (A. G. Burns et al., 1995; Prölss, 1980) near the local midnight sector. Then the strengthened equatorward meridional wind transports the composition disturbance equatorward to mid and low latitudes, and corotated toward later local time (A. Burns et al., 2006; Cai, Burns, Wang, Qian, Solomon, et al., 2021; Yu, Cai, et al., 2022; Yu, Wang, et al., 2022; Yu, Wang, Ren, Cai, et al., 2021; Yu, Wang, Ren, Yue, et al., 2021). During the transportation and corotation process, the formed disturbance can also be altered by background winds (Cai, Burns, Wang, Qian, Solomon, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%